PRACA TYMCZASOWA W ŚWIETLE PRAWA WSPÓLNOTOWEGO - Reda, Anna (Zeszyty Prawnicze, 2017)
Temporary Agency Work in EU Legislation Summary The article is about the history of the temporary agency work in EU Legislation. The temporary agency work is an increasingly significant form of employment It involves a triangular arrangement in which an agency intermediates between the worker and the user enterprise in arranging temporary employment assignments. The regulation of temporary work in the European Union has been contentious for over twenty years since the Commission first proposed a directive in in 1982. The negotiations of the European Social Partners towards an EU – wide Collective Agreement on temporary work were broken down in 2002. The adoption was never immediate. There is only one directive in EU, adopted in 1991 which concerns temporary work and fixed term contracts and deals with the safety at work (Directive 91/383 of 25 June 1991). The article attempts to shows the main causes for establishing a suitable framework for temporary workers in the EU and the reasons for ceasing the Directive Project in 2002. The author also analyses the most important issues of the proposal of a Directive: equal treatment of temporary workers, collective representation, training and development opportunities. It is also an actual issue at the moment because the Portugal Presidency started working on the project of a directive concerning temporary work in 2007.